Development of the Dengue Fever Prevention Paradigm in People of Kham Kaew Sub-District, So Phisai District, Bueng Kan Province, Thailand (Jurnal Pendidikan IPA Indonesia, 2020)
Environmental condition is very important for the Dengue Fever Prevention. People in this area lacked the knowledge, awareness of an environmental condition. To achieve sustainable control of the occurrence of dengue fever, therefore, this mixed methodology research was performed: 1) to gather general information related to the community environment for dengue fever prevention, 2) to develop a paradigm for dengue fever prevention, and 3) to compare the levels of knowledge, attitude, and community participation after attending a training course on dengue fever prevention. The gathering general information related to the community environment for dengue fever prevention was performed by survey method, 341 participants were recruited by using the Taro Yamane formula and stratified random sampling, subsequently, the model was developed for training. After that, the training and evaluation were implemented. Thirty-two volunteers participated in the training on dengue fever prevention. The testing instruments consisted of Knowledge Test Form, Attitude Test Form, and Dengue Prevention Participatory Test Form. The results indicated that the dengue fever prevention paradigm was supported by the following six factors: 1) having reliable data, 2) providing training on disease prevention, 3) having competent agents, 4) presenting the dengue prevention system to the community, 5) having people participation, and 6) having environmental management. Concerning the training on dengue fever prevention, the villagers’ post-test scores on knowledge, attitude, and participation in dengue fever prevention were significantly higher than their pre-test scores. This research increased the knowledge, attitude and participation of people after training on dengue fever prevention in their community.